2011
DOI: 10.1007/s13197-011-0301-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters for enhanced oil recovery from enzyme treated wild apricot kernels

Abstract: Present investigation was undertaken with the overall objective of optimizing the enzymatic parameters i.e. moisture content during hydrolysis, enzyme concentration, enzyme ratio and incubation period on wild apricot kernel processing for better oil extractability and increased oil recovery. Response surface methodology was adopted in the experimental design. A central composite rotatable design of four variables at five levels was chosen. The parameters and their range for the experiments were moisture conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The enzymatic pretreatment of apricot kernels with pectolytic and cellulolytic enzymes was investigated at the amount of moisture added during hydrolysis from 20 to 32 %. The highest value of increased oil recovery (2.53 %) was achieved at 23 % of the applied moisture relative to the weight of the substrate (130). The enzymatic hydrolysis of borage seeds with enzyme preparations Olivex and Celluclast was performed at a moisture content from 20 to 50 %.…”
Section: The Amount Of Added Process Watermentioning
confidence: 99%
See 2 more Smart Citations
“…The enzymatic pretreatment of apricot kernels with pectolytic and cellulolytic enzymes was investigated at the amount of moisture added during hydrolysis from 20 to 32 %. The highest value of increased oil recovery (2.53 %) was achieved at 23 % of the applied moisture relative to the weight of the substrate (130). The enzymatic hydrolysis of borage seeds with enzyme preparations Olivex and Celluclast was performed at a moisture content from 20 to 50 %.…”
Section: The Amount Of Added Process Watermentioning
confidence: 99%
“…with proteolytic, cellulolytic and pectolytic activity to improve aqueous extraction, organic solvent extraction and press extraction of the oil (3,4,6,9,10,(109)(110)(111)(112)(113)(114)117,118,130,132,133,137).…”
Section: Temperature Of the Enzymatic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Apricot kernels are important raw materials for the production of various products including oils and proteins. About 40-56 g of oil is present in 100 g of wild apricot kernel 1 . Apricot pits have been widely used in Chinese traditional medicine to treat asthma, aplastic anaemia, and tumours 2 .…”
Section: Introductionmentioning
confidence: 99%
“…They can also be used as lubricants, cosmetics, and surfactants 3 . Recently, researchers have examined the use of the wild apricot oil in many areas 1,3,4 . Although most of these studies suggest that the wild apricot oil is suitable for human consumption, they have found that wild apricot oil also contains up to 8% amygdalin 5,6 .…”
Section: Introductionmentioning
confidence: 99%